Parents' Beliefs about Medicines and Their Influence on Inhaled Corticosteroid Adherence in Children with Asthma - Jasna Petrić Duvnjak; Anita Ursic; Antonela Matana; Ivana Medvedec Mikic (MDPI AG, 2024)
The most widespread chronic condition observed amid children globally is asthma. Only half of children with asthma adhere to their prescribed inhaled corticosteroids (ICS) therapy. Parents' emotions and perspectives regarding asthma have an impact on inhalation corticosteroid adherence. The participants in this study were 148 parents of children with asthma, with the aim to redintegrate their beliefs about medicines in general and specifically of ICS and the impact on ICS adherence in children with asthma. Children were mostly male (66.9%), older than five years (58.8%), parents were female, mean age 38, employed, and with a history of consumption of some form of corticosteroids. Parents' answers show that 50% of them disagreed with the statement that medicines are addictive, and 90% agree that medicine helps many to live better. A percentage of 77.7% of parents acknowledge that their child's health relies on inhaled corticosteroids (ICS), and 86.5% of parents agree that these medications safeguard their child from worsening health. Most of the parents (93.2%) adhere to the guidelines and instructions of the doctor. In summary, parents who hold the belief that medicines are neither overused nor harmful tend to exhibit a higher adherence. Furthermore, those with elevated adherence levels express lower levels of concern regarding the use of inhaled corticosteroids (ICS) in their children's asthma therapy.